Incorporating psychoeducation, mindfulness and self-compassion in a new programme for binge eating (BEfree): Exploring processes of change. (March 2019) - Pinto-Gouveia, José; Carvalho, Sérgio A; Palmeira, Lara; Castilho, Paula; Duarte, Cristiana; Ferreira, Cláudia; Duarte, Joana; Cunha, Marina; Matos, Marcela; Costa, Joana
This study explores the efficacy of BEfree, a 12-session group intervention that integrates psychoeducation, mindfulness, compassion and value-based action, in a sample of overweight and obese women with binge eating disorder ( N = 31). We used repeated measures analyses of variance and explored processes of change in binge eating and eating psychopathology. At post-intervention, participants decreased in binge eating severity, eating psychopathology, external shame, self-criticism, psychological inflexibility, body image cognitive fusion and increased self-compassion and engagement with valued actions. These results were maintained at 3- and 6-month follow-up. The changes in binge eating were mediated by the changes in the psychological processes promoted by BEfree.